Sintering prevention and phase transformation of FePt nanoparticles - Ding, Y.; Majetich, S.A.; Kim, J.; Barmak, K.; Rollins, H.; Sides, P. (Journal of magnetism and magnetic materials, 2004)
self-assembled FePt nanoparticle arrays have been the subject of much interest due to their potential use as ultrahigh density magnetic storage media. Monodisperse FePt nanoparticles, as made, are FCC and must be annealed to induce the transformation. Unfortunately, this annealing process sinteres the particles together, destroying the key advantage over existing magnetic recording media. Two approaches attempted to overcome FePt nanoparticle sintering during the transformation to the high coercivity Ll0 phase, which currently limits the use of these nanoparticles in data storage media. High-pressure treatment of dilute nanoparticle solutions failed to prevent sintering due to surfactant decomposition above 360 C. By pre-annealing nanoparticle monolayers to decompose the surfactant, and then coating with an immiscible SiO2 matrix, sintering was prevented with annealing temperatures up to 700 C.